e-Learning in Higher Education Makes Its Debut in Cambodia: The Provincial Business Education Project - Abdon, Buenafe R.; Ninomiya, Seishi; Raab, Robert T. (International Review of Research in Open and Distributed Learning, 2007)
Developing countries face a number of challenges in their efforts to compete successfully in the new global economy. Perhaps the most critical resource needed to achieve these goals is trained human capital. While many developing countries are trying to address this need through traditional means, this may not be the most effective or efficient response. e-Learning has been suggested as an alternative approach that can overcome many of the challenges involved in reaching underserved students. But most educational institutions in developing countries are unfamiliar with eLearning, have low levels of computer availability, access, familiarity and Internet penetration which leads to skepticism about the feasibility of this approach. In an effort to assess the potential of e-Learning in meeting the needs for developing human capital in Cambodia, this paper reports on the experience and achievements of the Provincial Business Education through the Community Information Centers (CICs) project. Key findings are that e-Learning was able to successfully deliver tertiary educational opportunities to underserved provincial students, Cambodian students were able to overcome serious challenges and that female Cambodian students demonstrated superior performance in online classes. These results suggest that eLearning is an effective alternative for delivering tertiary education in Cambodia.